Evolution in motivation along medicine: want, choose, stay, exercise (Research, Society and Development, 2022)
The change in the reasons for starting and staying in Medicine during the pre-university entrance exam, beginning academic, graduating and active professional phases is due to the change in the perspective on Medicine during these periods. The objective of this review is to sketch an overview of these changes and, consequently, of individual motivation to continue in Medicine, in addition to exposing the resulting psychological effects and analyzing the distribution of physicians in Brazil. The literature used for this research was found in online databases on the following sites: VHL Brasil, PUBMED, Google Scholar and Scielo. The search terms were PROFESSIONAL CAREER, ENCOURAGEMENT, MEDICINE, DENSITY and MENTAL HEALTH. Articles published in English, Portuguese and Spanish were included, without time criteria. The articles found highlighted that 50.3% of students in the 1st year of the course are motivated by interest in science and that only 1.8% enter the course due to family pressure. In addition, it was observed that students in the basic cycle (43.6%) and clinical cycle (40.3%) tend to have higher rates of Common Mental Disorders compared to students in the last year of graduation (16.2%). . Furthermore, there was a higher density of physicians in the Southeast region, as it is an economic hub. Therefore, it is clear that Medicine is currently no longer sought after due to the status it provides, but rather because of the individual's own interest in a career with an opportunity for scientific development.